MODIFYING DOMINO CARDS TO INCREASE STUDENTS’ UNDERSTANDING OF THE USE OF POSSESSIVE ADJECTIVE AT JUNIOR HIGH SCHOOL - M Labib Al Halim (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2020)
This research aimed to know the use of modified domino card game as media to increase students understanding of the application of possessive adjective. The method of this research was classroom action research design proposed by Ferrance. The subjects were students of junior high school at MTs. Bahrul Ulum Turi Lamongan consisted of 28 students. The result showed that media domino card could stimulate students to be active and pay more attention. It effectively affected students’ achievement. The data showed that students’ achievement increase significantly from 57.86 in preliminary test to 76.57 in final test. Thus, it could be concluded that modified domino card could increase students understanding of the use of possessive adjective. It could also stimulate young students to be active and pay more attention to the lesson given